PERTAUTAN KEPENTINGAN ANTAR ELIT : STUDI TARIK ULUR KEPENTINGAN POLITIK ANTAR ELIT DALAM PEMBENTUKAN KABUPATEN PANGANDARAN - Fitriyani Yuliawati; Subhan Agung (Jurnal Ilmu Politik dan Pemerintahan, 2011)
Society certainly crave a more prosperous life, safe, peaceful, able to feed their family properly and wants other ideal. In today's the countries in the world of hopes and ideals via a mechanism known system and democracy. New mechanisms are emerging as the insistence of the Reformation is the insistence of Indonesia's regions to secede from the parent that we often refer to as autonomy. Insistence that gave birth to hundreds of new areas, both at the provincial and district / city emerged in Indonesia today. On one hand if we look at it positively, it is possible as the manifesto of a high sense of community ownership of their respective regions as well as the willingness to self-determination. On the other hand new problems arise as well as political risk, which appears sectarianism "sons of the soil" who gave birth to tribalism and excessive primordialism, resource conflict, conflict of interest, rampant corruption among local officials and that no harm is less conflict among local political elites in a fight over power and the existence of self and group interests in the name of the people. Risks in above which we discuss in this research study, with a focus study on the tug between the interests of local political elites in the division of the district of Pangandaran. With purposive sampling method of data collection and methods of interactive analysis, the study seeks to illustrate how the actual role, political intrigues and interests the desired political elites in the expansion of Pangandaran. How well conflict of interest occurs in the process of expansion of this district of Pangandaran. Hopefully this research is useful for those who want to further examine the processes and dynamics that occur, and how political elites play political roles.